2008
DOI: 10.3113/fai.2008.0601
|View full text |Cite
|
Sign up to set email alerts
|

Talonavicular Joint Approach to the Talar Body: A Cadaver Study

Abstract: This study shows that talar dome lesions can be reached with a minimally invasive method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Their study showed that the lesion of all regions of the talar body could be reached through a minimally invasive talonavicular approach by creating a small hole in the neck of the talus without the need for an osteotomy. 12 We did not use the talonavicular joint approach for any patients of the present series because reaching the lesion is more difficult with this approach, and it may also weaken the talus neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study showed that the lesion of all regions of the talar body could be reached through a minimally invasive talonavicular approach by creating a small hole in the neck of the talus without the need for an osteotomy. 12 We did not use the talonavicular joint approach for any patients of the present series because reaching the lesion is more difficult with this approach, and it may also weaken the talus neck.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches, such as talonavicular joint and medial malleolar osteotomy, have been proposed for this purpose. 12,21 However, owing to its rarity, there is no clear consensus regarding the optimal surgical approach for these lesions and the outcomes of treatment as well. In this study, we aimed to evaluate the functional outcomes and surgical complications following the treatment of the idiopathic talus IGC with curettage and bone grafting through a medial malleolus osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous anatomical and surgical technique studies have shown that both procedures are feasible and safe, with specific guidance for arthroscopic portal placement available. 9 , 11 , 23 , 24 For both approaches, the authors find that the use of an invasive distractor, such as the Hintermann spreader, is a critical step in achieving adequate working space for a successful treatment.…”
Section: Discussionmentioning
confidence: 99%